THE IMPACT OF MICROFINANCE SUPPORT ON THE DEVELOPMENT OF MANUFACTURING SMEs OPERATING IN WINDHOEK, NAMIBIA - Nautwima, Johanna Pangeiko; Asa, Romeo (Archives of Business Research, 2022)
Over the years, the superlative contribution of SMEs on economic growth predominantly in emerging states such as Namibia has been gaining considerable prestige at a rapid rate. However, deficient access to cost-effective financial adequacy remains a leading stumbling block that denies them the opportunity to survive in a competitive market, grow and develop above the average. That being true, the rate of SMEs’ failure continues to escalate precisely among those that are in their early stage of operation. To curb that specific issue, microfinance institutions (MFIs) intervene to provide dual supports through the delivery of financial and non-financial services. Access to such support helps SMEs to reduce their financial constraints, resulting in sound and viable development for businesses. In this respect, the central objective of this study was to investigate the impact of microfinance acquisition on SMEs’ development with reference to the manufacturing firms in Windhoek, Namibia. Evenly relevant, the study sought to further assess the effect of acquired microfinance support on competitiveness and finally devise suitable strategies that MFIs could adopt or adapt to improve the provision of microfinance services to penurious SMEs. The study employed a pragmatistic paradigm. Therefore, mixed research methods constituting both quantitative and qualitative approaches were utilised to successfully attain the threefold objectives of the study. 60 questionnaires were disseminated through emails to the sampled SMEs for data collection where only 44, accounted for 73% were considered for further analysis. Regarding financial support, the study assessed the matter based on technology enhancement, assets capital accumulation, job creation, business’ branches extension, and product development and expansion. Similarly, assessment on non-financial support was focused on managerial and leadership skills, as well as unblemished financial management. To test the nexus between microfinance support and SMEs’ development, multiple regression analysis was employed at 5% level of significance. Findings presented by the study revealed a positive strong relationship between the variables. More to that, the correlation between microfinance support and SMEs’ competitiveness was tested using correlation coefficient analysis and results found the variable to be statistically correlated. To this end, the study affirms that there exists a significant positive impact of microfinance support on SMEs’ development and competitiveness, implying that healthy and ample microfinance institutions are immensely essential to provide the required support lucratively, using the most satisfying strategies for a mutual benefit of the involved parties. Therefore, three strategies for improving the provision of microfinance support, constituting Public Credit Guarantee Schemes (PCGS); compensation of interest rate with the repayment period; and the provision of tools and equipment were designed. Also, the study recommended government intervention in formulating policies necessary for easing collateral requirements. More, MFIs are also advised to find ways for fastening their evaluation processes and give feedback on approval or disapproval of the application soon. They should also allow potential SMEs to borrow multiple times in a year or increase the principal amount. Finally, the study suggested future studies to focus on the role of the government in addressing SMEs’ financial constraints and use a longitudinal approach with a predominant focus on other sectors.